A Systemic Approach to Online Learning and Teaching Support - McGovern, Colum (Proceedings of the International Conference on Networked Learning, 1998)
Since 1996, Charles Sturt University has been investigating how best it would use the Internet to enhance learning outcomes for its more than 20000 students, most of whom study by distance mode; in particular how to improve student-lecturer and student- student communications. Rather than concentrating on developing fully online courses in a few discipline areas - some of which are already under way but require much time and resources - the decision was made to attempt to provide online support for all subjects of the University by the start of the 1999 academic year. The magnitude of this task is apparent from the number of subjects (more than 1600 annually) and the number of academic and support staff involved (more than 700). From the outset it was important to define precisely what was meant by online support for subjects. A distinction was drawn between an online supported subject and a fully online subject.